Validation of the Interreligious Forms of the Centrality of Religiosity Scale (CRSi-7, CRSi-14, and CRSi-20): Salience of Religion among Selected Youth in the Philippines - Castillo, Fides A. del ca. 20./21. Jh. (Religions, 2020)
The presence of different religions and the freedom of people to navigate the religious space shows that religion in the Philippines is not a monolithic entity. This study validated three versions of the Centrality of Religiosity Scale (CRSi-7, -14, and -20) which propose an adequate assessment tool for the diversity of religious belief systems co-existing in Philippine society. The sample (N = 514) was drawn from the young population of the country in an online survey. Descriptive statistics and Cronbach’s alpha values were calculated for the five subscales (ideology, intellect, experience, private and public practice) of the Centrality of Religiosity Scale. The factor structure of the interreligious Centrality of Religiosity Scale was tested using confirmatory factor analysis. The results show that CRSi-7 denotes internal consistency while CRSi-14 and CRSi-20 indicate good internal consistency. Models of CRSi-7, -14, and -20 show a good global fit. Despite two models of the CRSi-20 being identical in fit, the researchers defer to the CRSi-20 model with correlated factors since it is a simpler model. All versions of the CRSi demonstrate a valid and reliable measure for the centrality of religiosity in the Philippines and support the usefulness of the CRS for the study of religiosity.